1995
DOI: 10.1021/ic00112a028
|View full text |Cite
|
Sign up to set email alerts
|

New Hydride-Containing Mixed Metal-Gold Phosphine Clusters. Crystal Structures of [Pt(H)(CuCl)(AuPPh3)8](NO3) and [Pt(H)(CuCl)2(AuPPh3)8](NO3)

Abstract: The pyridine ligand of 3 can be substituted easily by Cl", Br" or SCN~ to give 4a, 4b, or 4c, respectively* The thiocyanate ligand of 4c is shown to be sulfur-coordinated to a gold atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 2 publications
4
16
0
Order By: Relevance
“…Inductively coupled plasma mass spectrometry (ICP-MS), which transfers all analytes into singly charged gaseous phase ions, can also provide useful information on the ratios of various elements in the study of heteronuclear clusters. 32,33 The ratios of Ag/Au acquired by ICP-MS are 13.6, 9.1, 7.3, 4.6 4.3 3.7, and 2.8 for 4, 6−10, and 13, respectively, which are in good agreement with the results calculated from the ESI-MS data (cf. Table S3).…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…Inductively coupled plasma mass spectrometry (ICP-MS), which transfers all analytes into singly charged gaseous phase ions, can also provide useful information on the ratios of various elements in the study of heteronuclear clusters. 32,33 The ratios of Ag/Au acquired by ICP-MS are 13.6, 9.1, 7.3, 4.6 4.3 3.7, and 2.8 for 4, 6−10, and 13, respectively, which are in good agreement with the results calculated from the ESI-MS data (cf. Table S3).…”
Section: ■ Experimental Sectionsupporting
confidence: 85%
“…Steggerda et al reported a similar growth reaction of [PtAu 8 (PPh 3 ) 8 ] 2+ using H 2 under basic conditions. , First, [Pt­(H 2 )­Au 8 (PPh 3 ) 8 ] 2+ is produced by dissociative adsorption of H 2 on [PtAu 8 (PPh 3 ) 8 ] 2+ and a proton is subsequently abstracted from [Pt­(H 2 )­Au 8 (PPh 3 ) 8 ] 2+ by the base (such as pyridine) to form [Pt­(H)­Au 8 (PPh 3 ) 8 ] + . Finally, a coinage metal cation can be introduced to form [Pt­(H)­(X) n Au 8 (PPh 3 ) 8 ] + (X = Au + , Ag + , Cu + ; n = 1, 2).…”
mentioning
confidence: 97%
“…For most of them the metallic frameworks can be derived from a Pt-centered Au 12 icosahedron by removing seven [41], six [555,556], four [556,558], three [548,[559][560][561], or two [556] vertices. Clusters with similar cores in which up to three gold atoms are replaced by atoms of another metal have also been reported, for example, Pt-Au 5 Pt 2 [550], Pt-Au 6 Hg [42], Pt-Au 5 Hg 2 [41], Pt-Au 8 Ag [556,562,563], Pt-Au 8 Ag 2 [563], Pt-Au 8 Cu [556,564] and Pt-Au 8 Cu 2 [564]. In another few compounds additional metal atoms are connected to an M 3 face of trimetallic frameworks derived from Pt-centered icosahedra, for example, Cu(Pt-Au 6 Cu 3 ) [565] and Ag 2 (Pt-Au 6 Recently, the first nanosized Au/Pt cluster, [(Ph 3 P) 2 Au 2 ] 2 Pt 13 (CO) 10 (PPh 3 ) 4 411, was reported; it contains a Pt-centered Pt 12 icosahedral cage capped by two (Ph 3 P)AuAu(PPh 3 ) units [567].…”
Section: Gold-group 9 Metal Compoundsmentioning
confidence: 99%
“…In the cation of 420 a difference was observed in the lengths of the heterometallic bonds, the radial Au-Cu bonds [2.564(2) -2.605 (2) Å] being significantly shorter than the tangential ones [2.706(2)-2.906(2) Å] [587]. Several other clusters with lower nuclearity display metallic frameworks which can be derived from a Pt-centered icosahedron by removing three or two vertices [556,564,565]. They include species with Pt-Au 8 Cu [556,564] and Pt-Au 8 …”
Section: Gold-copper Compoundsmentioning
confidence: 99%
See 1 more Smart Citation